FUNGSI PEMERINTAH KECAMATAN DALAM PENYELENGGARAAN KETENTRAMAN DAN KETERTIBAN UMUM ( STUDI KASUS PENERTIBAN HEWAN TERNAK DI KECAMATAN LINGGA) - Ulfah, Nurliza; Harahap, Tuti Khairani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Realizing a condition of peace and public order are both needed arrangement of maintenance and control of all aspects of social life including a ban on removing animals that may interfere with or affect the activities of daily life of society itself. This phenomenon raises many malasah among which damage the environment. farm animals eat the plants and damaging the courtyard and garden owned by residents to residents suffered losses. debris scattered in the streets also pollute the environment and interfere with the beauty of the city. even farm animals let loose this causing an accident to cause fatalities. Camat as leader of the Lingga district responsible for the implementation of peace and order assisted by Satpol PP as manager of control in field.The theory used in this research is the theory of organization by Subekhi & Jauhar (2013), are: planning, organizing, reporting and controlling. The research was conducted using qualitative descriptive method which is a description of the subject and the object, a system of thinking systematically about the fact description. Sampling technique used was purposive sampling with the collection of data are observation, interview and documentation. Informants in this study is Camat Lingga and Satpol PP Lingga Regency.The results of this research concluded that The Function of Lingga District Government have not been maximal running as expected local regulation. This can be seen from the presence of cattle owners still let their cattle wandering in the streets without controlling. Factors that influence the reform of farm animals is the lack of communication of the parties associated curbing farm animals, total resources are not accordance with the implementation of the reform activities, the absence of a budget, infrastructure and facilities to carry out reform and cultural community that ranching is not in accordance with the legislation.Keyword : the function of district government, peace, order